Label-free MSE proteomic analysis of chronic myeloid leukemia bone marrow plasma: disclosing new insights from therapy resistance - Pizzatti, Luciana; Panis, Carolina; Lemos, Gabriela; Rocha, Moisés; Cecchini, Rubens; Souza, Gustavo H. M. F.; Abdelhay, Eliana (Proteomics (Weinheim), 2012)
Chronic myeloid leukemia (CML) is a pluripotent hematopoietic disorder that is currently considered incurable. The tyrosine kinase product of the Philadelphia chromosome, P210 BCR‐ABL, provided a pathogenetic explanation for the initiation of the CML chronic phase and is the molecular therapeutic target for the disease. Imatinib mesylate, an orally available BCR‐ABL kinase inhibitor, can induce haematologic and cytogenetic remission of CML. However, imatinib resistance occurs frequently, resulting in relapse. New treatment strategies are focusing on resistant CML stem cells and the bone marrow stroma. The identification of novel pathways and mechanisms in the bone marrow microenvironment could significantly contribute to the development of such strategies. In this work, we used a high‐resolution label‐free MSE proteomic approach to identify differential protein expression in the CML bone marrow plasma of responsive and resistant patients. Oxidative lipid metabolism and regulation of the switch from canonical to noncanonical WNT signaling may contribute to CML resistance in the bone marrow compartment.